Food variety score is associated with dual burden of malnutrition in Orang Asli (Malaysian indigenous peoples) households: implications for health promotion. - Saibul, Nurfaizah; Mohd Shariff, Zalilah; Lin, Khor Geok; Kandiah, Mirnalini; Abdul Ghani, Nawalyah (Blackwell Publishing, 2009)
This paper reports on the presence of dual burden households in Orang Asli (OA, indigenous people) communities and its associated factors. A total of 182 OA households in two districts in Selangor with the required criteria (182 non-pregnant women of child bearing age and 284 children aged 2-9 years old) participated in the study. Height and weight of both women and children were measured. Energy intake and food variety score (FVS) were determined using three 24-hour diet recalls. While 58% were underweight and 64% of the children were stunted, the prevalence of overweight and obesity in women were 31% and 20% respectively. The percentage of dual burden households (overweight mother/underweight child) was 25.8% while 14.8% households had normal weight mother/normal weight child. The mean food variety score (FVS) was similar for women (7.0+/-2.1) and children (6.9+/-1.9). Dual burden households were associated with women's employment status (OR: 3.18, 95% CI: 2.65-5.66), FVS of children (OR: 0.71, 95% CI: 0.51-0.95) and FVS of women (OR: 1.39, 95% CI: 1.02- 1.89). The FVS of children (OR: 0.49, 95% CI: 0.25-0.89) and women (OR: 1.92, 95% CI: 1.64-2.77) remained significant even when dual burden households were compared to only households with normal weight mother/normal weight child. In these OA communities, food variety may predict a healthier diet in children, but may increase the risk of overweight and obesity in adults. Efforts to address households with dual burden malnutrition should consider promotion of healthy diets and lifestyle for all members.